Phosphate Solubilizing Rhizobacteria Could Have a Stronger Influence on Wheat Root Traits and Aboveground Physiology Than Rhizosphere P Solubilization - Elhaissoufi, Wissal; Khourchi, Said; Ibnyasser, Ammar; Ghoulam, Cherki; Rchiad, Zineb; Zeroual, Youssef; Lyamlouli, Karim; Bargaz, Adnane (Frontiers in Plant Science, 2020)
Limited P availability in several agricultural areas is one of the key challenges facing current agriculture. Exploiting P-solubilizing bacteria (PSB) has been an emerging bio-solution for a higher rhizosphere P-availability, meanwhile the above- and below-ground interactions that PSB would trigger remain unclear over plant growing stages. We hypothesized that PSB effects on plant growth may be greater on root traits that positively links with aboveground physiology more than the commonly believed rhizosphere P bio-solubilization. In this study, five contrasting PSB (Pseudomonas spp.) isolates (low “PSB1”, moderate “PSB2 and PSB4” and high “PSB3 and PSB5” P-solubilizing capacity “PSC”) were used to investigate above- and below-ground responses in wheat fertilized with rock P (RP) under controlled conditions. Our findings show that all PSB isolates increased wheat root traits, particularly PSB5 which increased root biomass and PSB3 that had a greater effect on root diameter in 7-, 15- and 42-day old plants. The length, surface and volume of roots significantly increased along with higher rhizosphere available P in 15- and 42-day old plants inoculated with PSB4 and PSB2. Shoot biomass significantly increased with both PSB2 and PSB5. Root and shoot physiology significantly improved with PSB1 (lowest PSC) and PSB4 (moderate PSC), notably shoot total P (78.38%) and root phosphatase activity (390%). Moreover, nutrients acquisition and chlorophyll content increased in inoculated plants and was stimulated (PSB2, PSB4) more than rhizosphere P-solubilization, which was also revealed by the significant above- and below-ground inter-correlations, mainly chlorophyll and both total (R=0.75, p=0.001**) and intracellular (R=0.7, p=0.000114*) P contents. These findings demonstrate the necessity to timely monitor the plant-rhizosphere continuum responses, which may be a relevant approach necessary to accurately evaluate PSB through considering below- and above-ground relationships; thus enabling unbiased interpretations prior to field applications.